New techniques and technologies in mining : proceedings of the School of Underground Mining, Dnipropetrovsʹk/Yalta, Ukraine, 12-18 September, 2010 /: proceedings of the School of Underground Mining, Dnipropetrovsʹk/Yalta, Ukraine, 12-18 September, 2010. (©2010) - Unknown
No abstract available